CDCA8 regulates ATP5F1A protein stability and malignant phenotypes in wilms tumor cells: Prognostic implications and mechanistic insights - Qiang Zeng; Junfeng Tao; Guangbei Peng; Lilu Qin; Shuzhen Wu; Chen Wang; Zhong Liu; Linshan Zeng (PLoS ONE, 2026)
Background Wilms tumor (WT) is a prevalent pediatric renal malignancy, yet its molecular mechanisms remain poorly defined. Identifying key prognostic genes and understanding their functional roles is critical for improving clinical management. This study aimed to identify prognostic genes in WT and to investigate whether ATP5F1A functions as a candidate downstream effector in a CDCA8-associated regulatory axis. Methods Differentially expressed genes (DEGs) were identified by analyzing RNA-seq datasets (GSE11151, GSE73209), comparing WT tissues with normal kidney samples. Functional enrichment was performed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. A protein-protein interaction (PPI) network was constructed, and hub genes were identified using Cytoscape. Prognostic significance was assessed through univariate and multivariate Cox regression analyses, and a risk prediction model was developed. External expression validation of candidate hub genes was performed using GSE11024 and GSE110696. CDCA8’s functional role in WT was validated by gene knockdown and overexpression experiments. Co-immunoprecipitation (Co-IP) and ubiquitination assays were conducted to explore the interaction between CDCA8 and ATP5F1A. Results A total of 987 DEGs were identified, with six hub genes—BUB1B, CDC45, CDCA8, KIF15, NDC80, and TOP2A—were identified. The exploratory risk score model stratified overall survival in the TARGET-WT cohort (HR = 2.973, Log-rank p = 0.000252), although time-dependent AUC values indicated modest discriminatory performance. CDCA8 was upregulated in WT tissues and associated with worse survival outcomes (HR = 2.03, p = 0.011). Functional assays suggested that CDCA8 knockdown suppressed malignant phenotypes in WiT49 cells. Mechanistically, CDCA8 knockdown reduced ATP5F1A protein levels without altering ATP5F1A mRNA expression, and this reduction was partially rescued by MG132. CDCA8 depletion was also associated with increased ATP5F1A ubiquitination, supporting a role for CDCA8 in maintaining ATP5F1A protein stability. Conclusions These findings suggest that CDCA8 may contribute to Wilms tumor cell phenotypes partly by maintaining ATP5F1A protein stability, providing preliminary evidence for a CDCA8-ATP5F1A regulatory axis in WT.